PENINGKATAN LITERASI ESTETIS DAN KOHESI SOSIAL MASYARAKAT MELALUI PUISI BERBASIS KOMUNITAS DI KOTA PONTIANAK - Hildawati Hildawati; Azizah Larasati; Roma Teressa; Andi Supiyandi; Joshua Fernando (Jurnal Abdi Insani, 2025)
Poetry is a form of reflective expression that plays an important role in conveying cultural values, healing the soul, and forming the collective identity of society. However, the perception of the general public currently still sees poetry as a complicated and exclusive art due to a rigid teaching approach and focus on structural aspects. This community service aims to open access and bring poetry closer to the general public. The poetry workshop was held offline in Pontianak involving participants from various age and professional backgrounds, in collaboration with the Pontianak Poetry Community. The method used is a community-based descriptive qualitative approach, emphasizing the active involvement of participants in the process of reading, writing, and reflecting on poetry, with a focus on personal experiences and emotional expression. The results show that poetry can be accessed and used as a medium for inclusive and reflective expression, is able to dismantle elitist stigma, and strengthens social connections between participants through a process of joint expression and appreciation. These findings strengthen the role of poetry as a means of aesthetic literacy that has the potential to increase expressive awareness and social cohesion in society.